Role of fungi, bacteria and microalgae in bioremediation of emerging pollutants with special reference to pesticides, heavy metals and pharmaceuticals - Sudipta Chakraborty; Avishek Talukdar; Satarupa Dey; Sayan Bhattacharya (Discover Environment)
Abstract Pesticides, heavy metals and pharmaceuticals are recalcitrant compounds, and are considered as emerging contaminants, having significant impacts on ecosystems and human health. Due to longer persistence in the environment and low biodegradability, these contaminants tend to bioaccumulate in both the terrestrial and aquatic ecosystems. Bioremediation has been gaining attention due to its effectiveness in removing toxic materials from the environment using various microorganisms like bacteria, fungi andalgae. Microorganisms use several biochemical and biophysical processes to reduce, remove, biodegrade and detoxify diverse range of contaminants. Microbial extra or intracellular enzymes play a significant role to transform the hazardous pollutants to their less toxic or non-toxic forms. Proper methods and useful strain of microbes are required to be selected for efficient ex situ or in situ bioremediation processes. This paper focuses on how microorganisms break down emerging pollutants like pesticides, pharmaceutical products and heavy metals. A brief account is given on the various species of fungi, bacteria and microalgae involved in bioremediation and associated mechanisms. The advantages and disadvantages of bioremediation are also discussed in this context, with concluding statements on the future perspectives and prospects of remediation of emergent contaminants.